A Comparative Evaluation Of Premedication With Flurbiprofen And Prednisolone On Post Endodontic Pain In Teeth With Symptomatic Irreversible Pulpitis: A Randomized Clinical Trial - Haq, Umair ul; Maqbool, Hassan; Rizwan, Zarnab; Sajid, Khadija; Nazir, Kiran; Khattak, Shakeel ur Rahman (Journal of Rawalpindi Medical College, 2023)
Background: Root canal treatment is an endodontic procedure that encompasses cleaning & shaping i.e. preparation of root canals followed by obturation of the prepared canals. Pain is a very common sensation that occurs few hours after root canal treatment (RCT). Objective: To evaluate and compare the efficacy of premedication with flurbiprofen and prednisolone on post-endodontic pain in teeth with symptomatic irreversible pulpitis. Materials and Methods: It is a randomized control trial study conducted in the department of Operative Dentistry & Endodontics, Sardar Begum Dental College, & Hospital Peshawar. Patients were randomly allocated into two groups i.e. A and B using coin flip technique. Thirty minutes before starting the endodontic therapy, single pretreatment dose of Flurbiprofen (100mg) was given to patients in Group A and Prednisolone (30mg) to patients in Group B. Patients’ pain intensity experience was measured using the visual analog scale (VAS) after root canal treatment. They were instructed to complete a pain diary at specific intervals (i.e. at 6, 12 and 24 hours after the commencement of treatment) in order to determine efficacy in both groups. Results: As per efficacy in both groups, in Group A, 44 (55%) showed effective results whereas in Group B, only 20 (25%) patients showed effective results. Conclusion: Single pretreatment dose of flurbiprofen has a more sustained effect in reducing post-endodontic pain as compared to prednisolone.